Individual and combined toxicity of imidacloprid and two seed dressing insecticides on collembolans Folsomia candida. Issue 5 (4th March 2023) - Lopes Alves, Paulo Roger; de Araújo, Rafael Soares; Ogliari Bandeira, Felipe; Matias, William Gerson
ABSTRACT: The aim of this study was to examine the chronic toxicity of imidacloprid (IMI), clothianidin (CLO) and fipronil (FIP) as a single exposure, as well as binary mixtures of IMI with CLO or FIP toward collembolans Folsomia candida, which are fauna present in the soil. Chronic toxicity assays were performed following an ISO guideline in a Tropical Artificial Soil (TAS), and the influence on the number and growth of the juveniles produced were determined. The range of nominal concentrations used in the tests with the individual compounds was 0.08–1.28 mg/kg (IMI), 0.079–1.264 mg/kg (FIP) and 0.007–0.112 mg/kg (CLO), whereas the mixture assays were performed with half the value used in the tests with individual compounds. Based upon single exposures, IMI produced a similar impact of reducing reproduction by 50% (EC50 ranging from 0.74 to 0.85 mg/kg) compared to FIP (EC50  = 0.78 mg/kg), whereas CLO was the most toxic to F. candida (EC50  = 0.08 mg/kg). Their mixtures generally resulted in a diminished effect on reproduction, as evidenced by the higher EC50 values. In contrast, in the case of the IMI+FIP combination at high concentrations at the EC50 level, a synergistic effect on toxicity was observed. The single exposure to the three insecticides and the mixture of IMI-FIP also decreased the size of generated juveniles, which was evidenced by the reduction in the proportion of large juveniles and increased proportion of small juveniles. However, both binary mixtures (IMI-FIP and IMI-CLO) presented antagonistic effects as evidenced by less than expected reductions in growth. Data on the toxic effects of IMI in a mixture with other seed dressing insecticides to collembolans provides useful information to environmental risk assessors by diminishing the uncertainties on the ecological risk of exposure to pesticides, enabling soil management degradation by utilizing multiple insecticides.